Мешок с несчастьями - Щеглов Дмитрий Алексеевич (Черный котенок, 2001)
Экземпляры: ф.6 (20181220) / Инвентарный номер: 2358 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Щ 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44